Implementation research: Understanding the application of learning following continuing professional education - Judith M. Ottoson . (Adult Education Research Conference, 1993)
This study operationally defines and refines a conceptual framework to analyze the application of learning following continuing professional education (CPE). The factors which affect application are deduced from implementation theory and research and induced from interviews with CPE participants. They are further tested with pre- and post-course questionnaires.